Applying Circle Game to Enhance Students’ Speaking Skill - Putri Denaya Side Ayu; Heri Hidayatullah; Sri Ariani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This Collaborative Classroom Action Research aimed at enhancing students’ speaking skill through the application of Circle Game. It was conducted in one cycle consisting of two meetings. The subject was the seventh of C class of SMPN 2 Alas Barat consisting of 22 students. The types of data were qualitative (acquiring observation during the learning process) and quantitative (speaking tests). The results qualitatively showed that the implementation of Circle Game enhanced the students’ speaking skills. Such improvement could be seen from their enthusiasm, their interesting feeling in various materials presented by the teacher, their active involvement. In the quantitative findings, the result also showed a higher value of the mean score of the post-test (77.34) rather than the pre-test (75.75). In conclusion, the use of Circle Game can improve students’ speaking skill.